(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The article discusses the key concepts of information technology, including such essential terms as information, data, computers, software, network technologies, the internet, cybersecurity, databases, cloud technologies, and artificial intelligence. Information technology has a significant impact on all aspects of human life, transforming the way we work, communicate, and process data. Understanding these concepts is crucial for IT professionals and the general audience who use digital technologies in everyday life.